"Of Course We Need to Help the Undocumented Immigrants!": Twitter Discourse on the (Un)deservingness of Undocumented Immigrants in the United States during the COVID-19 Pandemic. (October 2021) - Flores Morales, Josefina; Farago, Fanni
Undocumented individuals in U.S. society have been barred from access to federal economic relief during the global COVID-19 pandemic. Increased visibility of the vulnerability of undocumented individuals may provide a window of opportunity for inclusive policies. On the contrary, previous research about pro-immigrant sentiment shows that supporters of undocumented migrants advocate for them by using discourse that ultimately reifies their exclusion. The current study uses Twitter data collected from March to July 2020 to examine public discourse on undocumented immigrants during the pandemic. Our research question is: "How do Twitter users frame deservingness of undocumented immigrants during the COVID-19 pandemic?" We find that: (1) relief for undocumented immigrants continues to be contingent even in times of crisis, (2) economic productivity is a prerequisite of deservingness, and (3) anti-immigrant frames that scapegoat immigrants are flexible to the political and public health conditions of a historical period. Implications for policy are discussed.